2019
DOI: 10.3390/ijerph16183491
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Scabies and Stroke: A Population-Based Nationwide Study

Abstract: Background: Scabies is a commonly occurring infectious skin infestation that substantially impacts the quality of life, while stroke, which consists of a neurological deficit resulting from a lack of blood flow to the brain, carries sizable economic costs. The pathophysiologic mechanisms underlying both diseases involve inflammatory processes that are mediated by the immune system; however, no prior research has been conducted to explore the relationship between the two conditions. Methods: This population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…7 Similarly, another populationbased study showed an elevated risk of stroke in patients with a history of scabies during a 7-year follow-up period; however, patients with scabies also had a higher incidence of metabolic syndrome, which is a well-established risk factor for stroke alone. 8 More research is needed to elucidate the pathogenesis to better counsel patients with scabies, like the patient described in our case, about their imminent and long-term risks.…”
Section: Discussionmentioning
confidence: 88%
“…7 Similarly, another populationbased study showed an elevated risk of stroke in patients with a history of scabies during a 7-year follow-up period; however, patients with scabies also had a higher incidence of metabolic syndrome, which is a well-established risk factor for stroke alone. 8 More research is needed to elucidate the pathogenesis to better counsel patients with scabies, like the patient described in our case, about their imminent and long-term risks.…”
Section: Discussionmentioning
confidence: 88%
“…Our results supported our hypothesis that scabies infections may influence the progression of atherosclerosis and lead to subsequent AMI. Previous studies have shown that patients with scabies have an elevated risk of stroke, which is also a result of atherosclerosis [6]. Scabies is a skin infestation caused by the mite Sarcoptes scabiei; it is not only a simple, itchy skin disease but can activate many serious downstream systemic and life-threatening diseases [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified scabies-related complications, including chronic kidney disease (CKD) and chronic obstructive pulmonary disease (COPD) [2,4,5]. A nationwide study reported an increased risk of stroke in patients with scabies and suggested that this association may be due to immunopathological factors [6]. Immune and inflammatory responses are the basic pathophysiological mechanisms underlying scabies infections [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptom is severe itching due to skin lesions, which causes patients to scratch the lesions, resulting in secondary bacterial infections. In addition, it has been reported that there is a high risk of glomerulonephritis [ 2 ], chronic kidney disease [ 3 ], and stroke [ 4 ] after a major infection. Scabies mite infection spreads rapidly through direct skin contact, not only via patients but also via asymptomatic carriers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%